Assessing the effectiveness of barcoding for conservation of rare plant species in the Republic of Uzbekistan - F.U. Mustafina; D.N. Jamalova; D.E. Turdiev; G.T. Kurbaniyazova; A.Dj. Gaziev; N.Yu. Beshko; K.Sh. Tojibaev; Z.Z. Ibragimov; K.T. Boboev (Учёные записки Казанского университета: Серия Естественные науки)
This article presents, for the first time, a reference database of the nucleotide sequences for three DNA barcodes (ITS2, matK, and rbcL) of 65 rare and critically endangered plant species of the Republic of Uzbekistan (133 samples, two samples per species), including 23 monocots and 42 dicots. ITS2 region was proposed as the most variable, easily amplified and sequenced for both monocot and dicot species. Therefore, it was recommended as the main DNA barcode. The obtained reference database uploaded to the BOLD v4 platform should be useful for pharmaceutical companies, environmental and customs offices, as well as for phylogenetic research.